2001
DOI: 10.1002/ajh.1085
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided fine needle biopsy of the spleen: High clinical efficacy and low risk in a multicenter Italian study

Abstract: The aim of this study was to evaluate the clinical efficacy and safety of the ultrasoundguided fine needle biopsy (UG-FNB) of the spleen in a large population of patients. We collected retrospectively the findings concerning the application of UG-FNB of the spleen from eight Italian clinical centers that utilized this technique for at least ten years. A data schedule was sent to all centers to collect information about techniques, results, and complications of UG-FNB of the spleen. We analyzed 398 biopsy proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
0
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(131 citation statements)
references
References 16 publications
6
115
0
8
Order By: Relevance
“…Because imaging has not been demonstrated to be accurate for diagnosis, tissue samples from the spleen may be required to stage or diagnose malignancy or to assess for possible infection ( 1,2 ). Tissue samples can be obtained either by using splenectomy or percutaneous biopsy ( 2,(5)(6)(7). Splenectomy carries a relatively high reported morbidity (8.6%-37%) and mortality (0%-2.9%) rate, primarily because of infection (7)(8)(9).…”
Section: Search Strategymentioning
confidence: 99%
“…Because imaging has not been demonstrated to be accurate for diagnosis, tissue samples from the spleen may be required to stage or diagnose malignancy or to assess for possible infection ( 1,2 ). Tissue samples can be obtained either by using splenectomy or percutaneous biopsy ( 2,(5)(6)(7). Splenectomy carries a relatively high reported morbidity (8.6%-37%) and mortality (0%-2.9%) rate, primarily because of infection (7)(8)(9).…”
Section: Search Strategymentioning
confidence: 99%
“…No homem e no cão cada vez mais há estudos que empregam a PAAF para o diagnóstico deste tipo de neoplasia 4,22,23,24,25 . Nos casos de linfadenomegalia, este exame permite a diferenciação rápida entre processos reacionais benignos e neoplásicos 26 . Quando há suspeita de lesão ou alteração em órgãos internos, como vísceras abdominais ou torácicas, a PAAF também pode ser realizada com auxílio da ultrassonografia 26 .…”
Section: Introductionunclassified
“…Nos casos de linfadenomegalia, este exame permite a diferenciação rápida entre processos reacionais benignos e neoplásicos 26 . Quando há suspeita de lesão ou alteração em órgãos internos, como vísceras abdominais ou torácicas, a PAAF também pode ser realizada com auxílio da ultrassonografia 26 . Segundo a literatura, existe uma excelente correlação entre os resultados obtidos pela PAAF e por biopsias, tanto na classificação morfológica como na imunofenotipagem dos linfomas 25,27 .…”
Section: Introductionunclassified
“…Both sFNA and sCB are safe for patients with splenomegaly, and certain studies reported they exhibit excellent diagnostic accuracy in splenic malignancies, but a relatively low efficiency in splenic lymphoma (34,35). However, other studies indicated they have a rather low diagnostic yield on account of inadequate specimenin addition, in a review of 49 cases there was an overall complication rate of 16%, and complications such as bleeding and splenic rupture may have a fatal outcome (36,37).…”
Section: Discussionmentioning
confidence: 99%